Optimal parametric mixing analysis of active and passive micromixers using Taguchi method. (December 2019) - Shah, Imran; Su Jeon, Han; Ali, Muhsin; Yang, Doh Hoi; Choi, Kyung-Hyun
Mixing of fluids flowing through channels and chambers is a crucial step in chemical and biochemical reactions inside microfluidic devices due to laminar flow because of small size channel and chamber dimensions. Mixing can be enhanced by passive or active mechanism which makes convection dominant over diffusion. To address this challenge, the study proposes three novel mixing designs: passive mixer, active mixer and a combination of active and passive mixing. These designs mixing performance has been studied by numerical simulation using COMSOL 5.3. According to the preliminary results of the study, pure active micromixer design has superior mixing ability. The mixing ability was proved by concentration line plots, concentration contours and videos. In order to further optimize the mixing index of the pure active micromixer, Taguchi method is applied against various input parametric values for micromixer such as frequency, voltage and velocity. The velocity is required for two fluids to flow, while frequency and voltages are for providing an external energy for active mixing. A total of nine cases were analyzed; the two best cases out of nine were selected for comparing mixing index line plots. The result of the study conclude that pure active micro-mixer at an optimal set of parameters, frequency of 10 Hz, velocity of 0.05 mm s –1 and voltage of 0.5 V achieved 99.6% mixing index at t = 0.2 s.